Analysis of Discipline Implementation in Improving Employee Performance at PT. Bank Syariah Indonesia Medan Tomang Elok Branch - Vanessa, Vanessa; Rahmani, Nur Ahmadi Bi; Jannah , Nurul (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
In a company, human resources are one of the most important factors in determining the success of the company in achieving its goals. There must be work discipline in this endeavor. hard work. Discipline is the application of the application of rules and regulations that are understood as their responsibility, such as work schedules that have been set by a business entity and the tasks of being carried out by offices. This study uses qualitative data type by using purposive sampling technique. The data collection techniques used were observation and interviews with five participants as research information. The data analysis techniques used include SWOT analysis, observation and direct interviews with key informants and informants. The results of this study indicate that the work systematics at PT Bank Syariah Indonesia Kcp.Medan Tomang Elok is quite good, but in terms of work discipline there are still some employees who underestimate, starting from arriving not on time, misuse of time during breaks and many explanations of work responsibilities that are not in accordance with the duties of each employee. The performance of employees of PT Bank Syariah Indonesia Kcp. Medan Tomang Elok is quite good, with the existence of team work or collaboration between employees but with a very familial organizational culture resulting in employees not being professional and carrying out their responsibilities .